Picture archiving and communication system (PACS) characteristic on wired-line and wireless network for traffic simulation - Sanon Chimmanee (2018)
Recently, characteristic of HTTP, FTP, SMTP, VoIP and other Internet applications are widely studied. It is very useful for Traffic Engineering (TE) and Traffic Simulation. PACS (Picture Archiving and Communication System) has been becoming a popular healthcare application for accessing to medical images and patient's data diagnostics on a wired-line or/and wireless hospital network. However, a characteristic of PACS traffic on both wired-line and wireless network is rarely studied. Therefore, this paper studies and presents the characteristic of PACS over the wired-line and wireless network based on terms of the packet interval time, the packet size distribution (byte), as well as the effect of variable PACS flows (traffic load) on the ping packet loss, which are on the actual measurement. In addition, the packet interval time is represented in the form of PDF. The packet size distribution is represented in the form of histogram graph. It is very useful for Traffic Simulation. © 2013 IEEE.